TRANSFORMASI AGRIBISNIS BERKELANJUTAN: PEMBERDAYAAN PETANI DURIAN DAN KOPI DI DESA BRONGKOL, KABUPATEN SEMARANG - Pujiati, Amin; Sugiantoro, Bambang; Budiman, Kholiq; Retnoningsih, Amin (Jurnal Abdi Insani, 2025)
The purpose of the community service program under the Regional Empowerment scheme is to strengthen sustainable agribusiness for durian and coffee commodities through cultivation technology in Brongkol Village, Jambu District, Semarang Regency. The focus of the community service program is to address regional problems, namely economic problems. The problem-solving method is carried out in a participatory manner through socialization activities, training, technology application, mentoring, monitoring, and evaluation, as well as program sustainability in the Brongkol Village area. There are two target partners who receive benefits, namely Ajuning Tani (durian commodity) and Karya Bakti I Farmers Group (Robusta coffee commodity). The focus of the community service program for Ajuning Tani partners is addressing economic problems while Karya Bakti I Farmers Group partners are addressing tourism problems. The economic problem faced by partners is the lack of derivative products that can provide added value and increase income. The tourism problem faced by partners is the lack of readiness of superior products to become a pioneering tourism village. The solution designed to address the problem is carried out through several trainings, training in processing durian derivative products in the form of durian gelato, durian ice cream, durian candy and frozen durian. Coffee derivative products include dried coffee beans, ground coffee packaging, coffee perfume, and key chains made from coffee waste. Business management training, including digital business records and a coffee drying house, and marketing outside the region are expected to improve the quality and quantity of durian and coffee for target partners, positively impacting the environment and strengthening the economy of the Brongkol Village community, transforming it into an agrotourism village.